(untitled) (Current Horticulture, 2024)
The analysis of production and area under okra (Abelmoschus esculentus Linn.) in India showed a perceptible trend in growing preference of okra crops among farmers. There is a decline in growth rate of yield of okra. The analysis also showed that though there is a steady increase in the area as well in production under okra crops. The growth rate as well as forecasting from 2017-18 to 2020-21 showed the increasing trend. Graphical representation also showed the increasing trend of okra.